29 Capacity development to link the evidence base to improving regulation in road traffic injury prevention. (1st September 2016) - Murphy, Evelyn; Peden, Margie; Khayesi, Melecki
Abstract : Background: To support country work to improve national regulation on road traffic injury prevention, we developed various approaches and tools to enhance the capacity of staff in government and civil society organisations, mainly lawyers, to assess and develop evidence-based regulations. We use the term "regulation" in this presentation broadly to include laws that are enacted by national parliament and regulations issued by national or subnational ministerial or other executive branches of government. Methods: This presentation describes the approaches used to improve the skills, access to and use of evidence-based interventions to assess and improve regulations on road traffic injury prevention for lawyers and others involved in regulatory processes in public health or road traffic. Results: Since 2010, WHO has supported the improvement of road safely legislation in 12 countries with support from Bloomberg Philanthropies. In the early years of the capacity development programme (2012–2014), participants from 9 countries (Brazil, Cambodia, China, India, Kenya, Mexico, Turkey, Russian Federation, Viet Nam) were selected through a nomination process from WHO Regional and Country Offices. This phase focused primarily on providing face-to-face periodic training on skills and information on evidence-based road safety interventions. Starting in 2015 we launched a Legal Development Programme in 4 countries (China, Philippines, Thailand, United Republic of Tanzania) with the objectives of providing a range of learning opportunities for lawyers and other individuals involved in developing regulations and of improving their skills, access to and use of resources on evidence interventions to assess and develop evidence-based regulation. Participants were selected through a semi-competitive process taking into consideration their background, interest in the topic, the nature and extent of their involvement in public health or road safety regulation, and commitment to play an active role in improving legislation in public health or road safety in their country. The level of engagement of the Legal Development Programme members in regulatory mechanisms on the topic in country has also been enhanced. Conclusions: During 2012–2014 participants who regularly took part in face-to-face workshops showed longer-term and active involvement in improving road safety regulation in their country. Countries supported also showed better improvement in evidence-based regulation (either in the number of changes or in the extent to which the changes are in line with evidence). Although the impact of the Legal Development Programme has not yet been assessed, it has so far generated greater interest than the previous capacity development programme (through an increase in number of participating members since the launch) as well as more active involvement in various aspects of the road safety regulatory process.